Analisa Level Of Service Simpang Empat Bersinyal (Study Kasus Simpang Empat Kota Bengkulu) - Edito Dwiantoro (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2018)
Congestion is often encountered during rush hour every day, when entering the clock hours where the number a vehicles going towards a certain will be more. the traffic is crowded with students, college students, workers and employees leaving for schols, campuses, workplaces and goverment offices so often do not comply with traffic rules at the intersection, especially in the city of Bengkulu frequent congestion di simpang IV in the city of Bengkulu Data collection using survey method is by conducting direct observation of real field situation, that is by calculating the length of queue and the length of queue of vehicles on each of the intersectian as well as measurement of the width of the road in each arm reviewed. This is absolutely necessary in oder to Anow the actual condition at this time, so it is hoped that there will be no mistake in evoluation and planning. Data obtained from this survey activily is called primary data The performance of service level of Simpang kompi at 07.0-14.00 is at service level of C with value of V/C 0. 5-0.41 while at 16.00-18.00 with value of V/C ratio 0,43 indicate that traffic at intersection sill at a satisfactory rate of speed